SUPERIOR MESENTERIC ARTERY SYNDROME COUPLED WITH RENAL NUTCRACKER SYNDROME - Sana Sharafat Ali; Waqar, Shazad Hussain; Sajid Ali Shah; Isbah Rashid; Fatima Shahzad (Journal of Ayub Medical College Abbottabad, 2024)
An acute vascular angle between the superior mesenteric artery and the Aorta may compress the third part of the duodenum (SMA Syndrome) and the Left Renal Vein (Renal Nutcracker Syndrome). Usually, patients are young females with a lean stature. Symptoms of outlet obstruction and pelvic congestion syndrome may be present. Our patient presented with bilious vomiting and unintentional weight loss for the last 6-8 months. On further inquiry, she had dysmenorrhea and left flank pain associated with microscopic haematuria. Duodenojejunostomy with Left Renal Vein (LRV) re-positioning was performed. She recovered uneventfully and has improved intake with mild or no pain troubling her at 6 weeks of surgery.